2022
DOI: 10.1183/13993003.01469-2021
|View full text |Cite
|
Sign up to set email alerts
|

Plasma cell but not CD20-mediated B-cell depletion protects from bleomycin-induced lung fibrosis

Abstract: Idiopathic pulmonary fibrosis (IPF) is an interstitial lung disease associated with chronic inflammation and tissue remodelling leading to fibrosis, reduced pulmonary function, respiratory failure and death. Bleomycin (Blm)-induced lung fibrosis in mice replicates several clinical features of human IPF, including prominent lymphoid aggregates of predominantly B cells that accumulate in the lung adjacent to areas of active fibrosis. We have previously shown a requirement for B cells in the development of Blm-in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(10 citation statements)
references
References 62 publications
3
7
0
Order By: Relevance
“…16E ). This suggests that plasma B cells in the epicardium may contribute to ECM formation, consistent with a previous study showing the role of plasma B cells in fibrosis 82 .…”
Section: Resultssupporting
confidence: 92%
“…16E ). This suggests that plasma B cells in the epicardium may contribute to ECM formation, consistent with a previous study showing the role of plasma B cells in fibrosis 82 .…”
Section: Resultssupporting
confidence: 92%
“…Anti-CD20 antibody rituximab treatment of B-cell tumors and related autoimmune diseases [21]. Inhibition of CD20 B cells in bleomycin-induced pulmonary brosis by removal of mature B cells by ablative therapy [22]. CD28 on activated Tregs is a CD28 subpopulation distributed on the surface of regulatory T cells, whose expansion is dependent on the T-cell receptor (TCR) and the CD28 signaling pathway, generating antigen speci city and effectively inhibiting the proliferation of effector T cells.…”
Section: Discussionmentioning
confidence: 99%
“…B-cell depletion therapy has been shown to suppress excessive inflammation in inflammatory diseases, but this approach eliminates nearly all B cells in the body and is not suitable for sepsis ( Lee et al, 2021 ). However, recent studies have shown that treatment of mice with plasma cell-depleted bortezomib, but not with anti-CD20-B cells ablation, prevents bleomycin-induced pulmonary fibrosis ( Prêle et al, 2022 ). Similarly, lethally irradiated mice lacking MZ B cells were resistant to LPS-induced endotoxic shock ( Honda et al, 2016 ).…”
Section: Clinical Applications and Therapeutic Potential Of B Cells I...mentioning
confidence: 99%